From Preferential Trade Arrangements to Free Trade Agreements: One of the Downturns of Cooperation in International Relations? - Jose Jaime Baena-Rojas; Susana Herrero-Olarte (Social Sciences, 2020)
Since the signing of the General Agreement on Tariffs and Trade (GATT) and the creation of the World Trade Organization (WTO), preferential trade agreements (PTAs) have been an interesting tool to promote international cooperation through the granting of non-reciprocal and/or unilateral tariff preferences by developed countries to developing countries. These international agreements have tended to generate critical trade dependencies for the receiving countries. Due to the circumstances of world trade and due to the lack of interest of the grantors to maintain this type of tariff preference, these developing countries are forced to renegotiate their PTAs into to free trade agreements (FTAs). To demonstrate this, we conducted a qualitative analysis to characterize the behavior of PTAs and their impact on the configuration of FTAs and to obtain indicators and trends. The results suggested a predominance of FTAs and a decline in PTAs. This was done to maintain access to the markets within those granting countries, which also became the main trading partners of these PTA recipient countries.